Establishment of entrepreneurship and business security in the Republic of Kazakhstan - Simonov, S.G.; Zhanuzakova, S. (KSU Publ., 2017)
This article describes the stages of entrepreneurship development in the Republic of Kazakhstan, also the business security issues and the analysis of the evolution of the legal framework of entrepreneurial activity are considered. The laws adopted since the independence, strategic plans, and the state programs of business and security support are presented in this article.During the years of Kazakhstan's independence more than a dozen laws were adopted, in order to maintain and ensure safe business operations. Currently, legislation on business activity is a vast array of regulatory legal acts in various industrial branches, which are organized into a single database in the form of the Civil Code and the Business Code of the Republic of Kazakhstan. In recent years, in order to improve the competitiven c v ess of domestic enterprises and ensuring its security programs such as: Nation Plan «100 concrete steps», «NurlyZhol» for 2015-2019, «BRM-2020» were developed. These programs are aimed at the preservation of existing and creation of new businesses, as well as providing them with non-financial support for the information and analytical support, the development of entrepreneurial capacity, introduction of innovative technologies, increasing the productivity of enterprises.The dynamics of the number of registered small and medium-sized businesses is analyzed. Several destabilizing factors constraining the growth of medium and large businesses is are presented.Growth in the number of registered enterprises confirms the effectiveness of the reforms in the country. But this trend is only characteristic of subjects of small farms, which is not true for the medium and large business. Various types of destabilizing factors prevent the growth of the last ones, these factors reduce the functioning of the security and restraining further growth, such as logistics, lack of funding, administrative barriers and the mentality of the business environment in the region. A number of destabilizing factors constraining the growth of medium and large businesses are identified. These factors require more attention and support from the state; favorable conditions for the safe operation and further development of business in Kazakhstan should be created.
Кəсіпкерліктің қалыптасуы жəне Қазақстан Республикасындағы бизнес қауіпсіздігін қамтамасыз ету
Становление предпринимательства и обеспечение безопасности бизнеса в Республике Казахстан
Keywords: entrepreneurship; security; economic reform; the threat; risk; factor; state support; business entities